Sifat-sifat Lentur Papan Partikel Komposit Kulit Kacang Tanah/Epoksi - Sudarisman, S; Rahman, Muhammad Budi Nur; Darmawan, Awang (Prosiding University Research Colloquium, 2018)
Flexural properties, i.e. load-displacement response, flexuralstrength, failure strain and modulus, of peanut shell particle-reinforced epoxy composites have been investigated. Four different fiber contents, i.e. 0, 20, 30 and 40 vol%, have been fabricated by means of press mold technique, and two particle sizes of passing through of mesh 11 but not for mesh 16, and passing through 16 sievers have been utilized. Specimen preparation and testing were carried out in accordance with the ASTM D1037. Failure modes were evaluated by closely observing representative photo macrographs of randomly selected failed specimens. The result revealed that the finer the particles, the higher the flexural strength and flexural modulus. To the contrary, finer particle size resulted in lower strain to failure. Almost all specimens show considerably linear lateral force-deflection relations up to close to failure. Specimens being produced using coarser particles achieved the highest flexural strength and modulus of 38.69 MPaand 2.141 GPa, respectively, at Vf = 20%, while the highest flexural strain to failure of 2.48 % was achieved atVf = 40%. Specimens being produced using finer particles achieved the highest lentur strength and strain to failure of 43.77 MPa and 2.01 %, respectively, at Vf = 30%, while the highest lenturmodulus of 2.618 GPa was achieved at Vf = 40%. Unlike pure epoxy specimens which underwent brittle fracture along with broken into pieces, those filled with peanut particles underwent singleplane brittle fracture.